إشكالية التفسير القضائي لقواعد القانون الجوي في القانون الإماراتي - Abdalla Salim Alketbi; Nisar Mohammad Ahmad; Azman Ab. Rahman; Noor Dzuhaidah Osman (Usuli Faqih Research Centre PLT, 2024)
Perdana: International Journal of Academic Research Volume: 18 No: 1 (page: 65-76)